Penggunaan Let’s Read Sebagai Media Pembelajaran Untuk Meningkatkan Kemampuan Literasi Siswa Sekolah Dasar - Rika Herlina; Ajo Sutarjo; Muhammad Hanif (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2023)
This research was conducted to determine the effect of using Let’s read on students' literacy skills. Based on a pre-survey conducted by researchers at SDN Jelambar 06, the literacy ability of students in this school is still very low, because teachers have not carried out reading habituation activities at the beginning of the lesson and many students do not want to cultivate reading activities as a daily habit. This happens because of the lack of support for the media in literacy activities. Given these problems, a strategy that can help teachers maximize media in improving literacy skills is the Let’s read.media Let’s read can help teachers because it has features as well as reading books that are packaged briefly but can foster a sense of interest and interest in students in reading activities. Researchers conducted quantitative research using experimental methods. The data were observed by grade 5 students, amounting to 32 people. The data analysis technique used is normality test and hypothesis testing using paired sample t-test. The results of the study obtained the value of Sig.(2-tailed) of the two paired sample t-test 0.000.means that there is a significant difference between the level ratio before and after treatment . It can be concluded that the use of Let’s read has an effect on improving the literacy skills of 5th graders at SD Negeri Jelambar 06.